Comparison of apparent diffusion coefficient values in sentinel lymph nodes versus primary tumors for gastric cancer N staging - Yan, Liang-liang; Li, Jing; Qu, Jin-rong; Zhang, Hong-kai; Zhang, He; Yu, Wei-hui (Frontiers in Oncology, 2025)
PurposeTo explore the differences in apparent diffusion coefficient (ADC) values based on the primary tumor and sentinel lymph node (SLN) for predicting N stages of gastric cancer (GC).MethodsOne hundred and sixty histopathologically confirmed GC patients between April 2021 and October 2024 were prospectively recruited. Preoperative DW-MRI was performed, and ADC values from primary tumors (ADCT) and SLNs (ADCLN), along with their relative ratios (rADCT, rADCLN), were measured. Differences in these parameters across N stages were analyzed using the Kruskal-Wallis test. Receiver operating characteristic analysis was used to evaluate their diagnostic performances for predicting N0 vs. N1–3 stages, N0 + 1 vs. N2 + 3 stages, and N0 + 1 + 2 vs. N3 stages.ResultsSignificant differences were observed in ADCT, rADCT, ADCLN, and rADCLN values across N stages (all p < 0.001). The AUC values of ADCT, rADCT, ADCLN, and rADCLN for predicting N0 vs. N1 + 2 + 3 stages were 0.753, 0.727, 0.782, 0.792, respectively. The AUC values of ADCT, rADCT, ADCLN, and rADCLN for predicting N0 + 1 vs. N2 + 3 stages were 0.776, 0.767, 0.844, 0.837, respectively. The AUC values of ADCT, rADCT, ADCLN, and rADCLN for predicting N0 + 1 + 2 vs. N3 stages were 0.797, 0.792, 0.857, 0.848, respectively.ConclusionsBoth primary tumor- and SLN-derived ADC values can effectively differentiate N stages among patients with GC. SLN-based ADC parameters exhibit superior diagnostic performance compared to primary tumor-based measurements in stratifying N-stage progression.